Routledge Handbook of Human Resource Management in Asia (Taylor & Francis, 2018)
Asia; Cooke; handbook; HRM; human; management; resource
English
Keywords: Ethnic studies; Personnel & human resources management; Regional studies; Asia; Cooke; handbook; HRM; human; management; resource